Fishes - Jongkar, Grinang (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd, 2025)
The Niah River, spanning a catchment area of 134,940 hectares and extending over 113.12 km, plays a critical role in the region’s ecosystem. Niah National Park, covering 3,138 hectares (approximately 2% of catchment area) supports a variety of aquatic habitats, including slow-flowing tributaries, swamps and cave passages within the Niah Caves Complex. The Niah River itself remains turbid throughout the year, primarily due to extensive land use activities, particularly oil palm plantations. While land use impacts are evident within the drainage system, the pristine forests within the Park provide a buffering effect, mitigating to some extent, these disturbances. The historical significance of the area is highlighted by visits from notable figures such as Tom Harrisson, a former Sarawak Museum Curator, who explored the region in 1960 and 1963, and Lord Medway (at present, the Earl of Cranbrook), who visited the site on 22 August 1959. Although the Park’s geological history is well known, knowledge about its ichthyofauna remains limited. To date, approximately 21 fish species from 12 families have been recorded from the main river, tributaries and swampy habitats within the area (see Checklist). Fish found outside the Park serve as a vital protein source for Iban communities living along its perimeter. More extensive explorations are expected to lead to the discovery of additional fish species to the list appended.